Survival in breast cancer patients with a delayed DIEP flap breast reconstruction after adjustment for socioeconomic status and comorbidity. (October 2021) - Coudé Adam, H.; Docherty Skogh, A.C.; Edsander Nord, Å.; Schultz, I.; Gahm, J.; Hall, P.; Frisell, J.; Halle, M.; de Boniface, J.
Abstract: Purpose: Overall survival in breast cancer patients receiving a delayed deep inferior epigastric perforator (DIEP) flap breast reconstruction is better than in those without delayed breast reconstruction. This study aimed at determining the impact of socioeconomic status (SES) and comorbidity on these observations. Materials and methods: This matched cohort study included all consecutive women undergoing a delayed DIEP flap reconstruction at Karolinska University Hospital, Sweden, between 1999 and 2013. Controls had not received any delayed breast reconstruction and were relapse-free after a corresponding follow-up interval. Matching was by year of and age at mastectomy, tumour stage and lymph node status. Charlson Comorbidity Index (CCI) and socioeconomic data were obtained from national registers. Associations with breast cancer-specific (BCSS) and overall survival (OS) were investigated by Kaplan-Meier survival estimates and Cox proportional hazard regression analysis. Results: Women in the DIEP group (N = 254) more often continued education after primary school (88.6% versus 82.6%, P = 0.026), belonged to the high-income group (76.0% versus 63.1%, P < 0.001), were in a partnership (57.1% versus 55.7%, P = 0.024) and healthier (median CCI 1.00 (range 0–13) versus 2.00 (range 0–16), P = 0.021) than the control group (N = 729). After adjustment for tumour and treatment factors, SES and comorbidity, OS remained significantly better for the DIEP group than the control group (HR 2.27, 95% CI 1.44–3.55). Conclusion: Women with a delayed DIEP flap reconstruction are a subgroup of higher socioeconomic status and better health. Higher survival estimates for the DIEP group persisted after adjusting for those differences, suggesting the presence of further unmeasured covariates. Highlights: Women with a delayed DIEP flap reconstruction have a higher socioeconomic status. They also have less comorbidity than women with no delayed reconstruction. Superior survival in DIEP patients is not eliminated by adjustments for such differences. Unmeasured selection to the reconstructive process may explain observed survival differences.